IMPLEMENTASI LITERASI DIGITAL DALAM PEMBELAJARAN MATEMATIKA - Theofilus Carolus Dima; Yepi Sedya Purwananti (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to describe the implementation of digital literacy in mathematics learning at SMP Kristen Sendang. This study uses a descriptive qualitative method with data collection techniques in the form of questionnaires and documentation. The subjects of this study were 1 mathematics teacher and 40 students in grades VII, VIII, and IX. The results of the study indicate that digital literacy has been implemented through the use of technological devices, digital-based learning media, and online learning resources. Teachers play a role in guiding students to utilize technology effectively in understanding mathematical concepts, while students demonstrate the ability to access, analyze, and utilize digital information for learning. However, several challenges such as limited access to technology and variations in students' levels of digital understanding are obstacles that need to be considered. This study concludes that the implementation of digital literacy in mathematics learning has great potential to improve the quality of the teaching and learning process, but requires support from infrastructure and increased digital skills for teachers and students.